Trinidad and Tobago : an evaluation of macroeconomic management and demand during oil shocks - Holder, Carlos ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Evaluated macroeconomic policy during two windfall periods in Trinida and Tobago